School-Based Caries Prevention, Tooth Decay, and the Community Environment. (April 2018) - Ruff, R.R.; Niederman, R.
The school and community context can contribute to inequity in child oral health. Whether the school and community affect the effectiveness of school-based caries prevention is unknown. The association between the school and community environment and dental caries, as well as their moderating effects with school-based caries prevention, was assessed using multilevel mixed-effects regression. Data were derived from a 6-y prospective cohort study of children participating in a school-based caries prevention program. For the school and community, living in a dental-shortage area and the proportion of children receiving free or reduced lunch were significantly related to an increased risk of dental caries at baseline. Caries prevention was associated with a significant per-visit decrease in the risk of untreated caries, but the rate of total caries experience increased over time. Caries prevention was more effective in children who had prior dental care at baseline and in schools with a higher proportion of low socioeconomic status students. There was significant variation across schools in the baseline prevalence of dental caries and the effect of prevention over time, although effects were modest. The school and community environment have a direct impact on oral health and moderate the association between school-based caries prevention and dental caries. Knowledge Transfer Statement: School-based caries prevention can be an effective means to reduce oral health inequity by embedding dental care within schools. However, the socioeconomic makeup of schools and characteristics of the surrounding community can affect the impact of school-based care.